TASK-BASED LANGUAGE LEARNING: IMPLEMENTING A TASK-SUPPORTED SYLLABUS - Megawati, Fika; Alwiyasa, Rahmatul Khalik (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
Task-Based Language Teaching has emerged as an innovative approach to language learning, emphasizing the use of meaningful tasks to facilitate language acquisition. This method not only fosters engagement among learners but also caters to their specific needs and proficiencies, thereby promoting a more dynamic and effective learning environment. The study employed a qualitative research design utilizing semi-structured interviews to gather data on learners' experiences and outcomes associated with task-based activities. Participants comprised language learners from diverse backgrounds who engaged in a variety of task-based activities designed to reflect their linguistic needs and cultural contexts. The findings showed that students generally found the task-based activities engaging and relevant to their language learning needs, as the tasks often mirrored real-life situations, which increased their motivation and facilitated a deeper understanding of language use in authentic contexts. The incorporation of such authentic tasks not only enhanced the learners' motivation but also encouraged the transfer of skills to real-world communication scenarios, demonstrating the critical link between task relevance and communicative competence among language learners.